Sistema biomédico para vertebroplastia - Márquez Miranda, Mario; Ferreyro Irigoyen, Roque (Revista Mexicana de Ingenieria Biomedica, 2004)
In this work, a design of a biomedical system is presented by choosing it with Pug’s matrix selection method. It is capable of distance injections for percutaneous vertebroplasty. This system is thought to solve two complex vertebroplasty problems: injecting a biomaterial suspension, polymethyl-methacrylate (PMMA) through fractured vertebrae via transpedicular or oblique method, using a biopsy needle and a syringe of 3 ml and set apart physician to a suitable distance in order to over expositions from ionic radiation.